Writing Personal Trauma in Young Adult Fiction: Benjamin Zephaniah’s Refugee Boy and Siobhan Dowd’s Solace of the Road (American & British Studies Annual, 2017)
In recent decades, the findings of trauma studies have been used in analyzing literary texts depicting trauma. While most critical attention is devoted to so-called historical or collective trauma (such as the Holocaust) and its long-time effects on survivors, there are novels, particularly coming-of-age novels, addressing complex issues of personal trauma. Analyzing Benjamin Zephaniah’s Refugee Boy (2001) and Siobhan Dowd’s Solace of the Road (2009), this paper centers on personal (individual) trauma such as loss, child abuse and/or abandonment, and on traumatic memory in connection with identity formation of a teenage protagonist. It also deals with the textual means of writing trauma and reflects on the category of young adult literature under which both novels were marketed, arguing why Zephaniah’s novel fits the category while Dowd’s can be seen as a crossover novel.
Keywords: trauma; coming-of-age novel; writing trauma; young adult novel; crossover novel; Benjamin Zephaniah; Refugee Boy; Siobhan Dowd; Solace of the Road